Islamic Republic of Afghanistan : Fifth Review Under the Staff-Monitored Program and Request for an Extension. (IMF Staff Country Reports; Country Report, 2005)
This paper discusses the Fifth Review Under the Staff-Monitored Program (SMP) for Afghanistan. The authorities met all the end-June 2005 indicative quantitative targets and structural benchmarks under the SMP. Economic developments were broadly in line with the program projections made at the time of the fourth review. The growth estimate for 2004/05 was adjusted slightly upward, to 8 percent, to account for a more buoyant manufacturing sector. Economic activity during the first quarter of 2005/06 appears to be consistent with the 14 percent growth projection for the year.